2014
DOI: 10.1177/0956462414563627
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma gene polymorphism influences the frequency of aChlamydia trachomatiscervical infection in young women

Abstract: Cervicitis associated with Chlamydia trachomatis is frequent worldwide, but the factors determining susceptibility to infection remain incompletely determined. We evaluated whether a functional single nucleotide polymorphism at position +874 in the gene coding for interferon gamma (rs2430561) influenced the likelihood of having a cervical C. trachomatis infection. This was a cross-sectional study of 142 sexually-active women attending a general gynaecology service on the outskirts of the city of Fortaleza in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…Individual variations in the ease of IFN-␥ induction and the extent of its production in response to specific infections may determine which of the two mechanisms predominates. We have demonstrated that women positive for a single nucleotide polymorphism associated with elevated IFN-␥ production (rs2430561) had a lower likelihood of having a C. trachomatis cervical infection than did women who were negative for this variant allele (35). Thus, the extent of IFN-␥ production in individual women most likely also influences the likelihood of chlamydial survival.…”
Section: Trachomatis Persistencementioning
confidence: 90%
“…Individual variations in the ease of IFN-␥ induction and the extent of its production in response to specific infections may determine which of the two mechanisms predominates. We have demonstrated that women positive for a single nucleotide polymorphism associated with elevated IFN-␥ production (rs2430561) had a lower likelihood of having a C. trachomatis cervical infection than did women who were negative for this variant allele (35). Thus, the extent of IFN-␥ production in individual women most likely also influences the likelihood of chlamydial survival.…”
Section: Trachomatis Persistencementioning
confidence: 90%
“…Таким чином, при зниженні рівня ІФН-γ після елімінації ЕТ, РТ, що увійшли в персистентний стан, можуть знову почати ділення [18,19]. Індивідуальні генетично детерміновані особливості утворення ІФН-γ також впливають на інфікування C. trachomatis, характер клінічного перебігу та розвиток наслідків [20].…”
Section: хламідійна інфекція сучасні дані про патогенезunclassified